Serdang Malay’s Flora Lexicon of Masam (Sour) Category: The Representation of Environmental Treasury - ., Faridah (KnE Social Sciences, 2018)
This paper is aimed at analyzing Serdang Malay’s richness in the flora lexicon of the masam (sour) category. The method is qualitative in which the data were obtained from interviews, participant observation and documentation. This study uses ecolinguistic parameters, namely, interrelation, interaction, interdepedence, diversity, and environment. The results indicate that there are only three masam categories consisting of 21 lexicons. The lexicons in first category include gelugur acid (asam gelugur), binjai acid (asam binjai), star fruits, tamarind, nutmeg, kasturi lime (limau kasturi), citrus (limau nipis), and purut lime (limau purut). The second category is well known for appetizers, namely, orange (limau manis), grapefruit (limau bali), jelly guava (jambu bertih), water guava (jambu air), guava bell (jambu lonceng), guava boll (jambu bol), milk guava (jambu susu), and guava (jambu klutuk). The last category is considered as mild halua (sweets), such as kecapi fruit, ambarella fruit (kedondong), rukam fruit, lacy fruit (buah renda), and boni fruit. Keywords: flora lexicon, sour category, Serdang Malay community